Evaluation on User Perception Effect based on Interaction Techniques in the Stereoscopic Environment - Dino Caesaron; Rio Prasetyo Lukodono; Yunita Nugrahaini Safrudin (CommIT (Communication and Information Technology) Journal, 2021)
The interaction of user performance with three-dimensional (3D) objects has become an important issue in the recent development of virtual reality applications. Additionally, the basic conviction of current Virtual Reality (VR) supports the development of the viable interface between humans and machines. The research focuses on the user’s interaction technique by considering two approaches (direct and indirect interaction techniques) for the users while interacting with threedimensional objects. Numerous possible uses can benefit from virtual reality by considering a few fundamental visual and cognitive activities in the Virtual Environment (VE), such as the interpretation of space that users of clear and indirect perception are not well established. The experiment is performed in a stereoscopic environment using a reciprocal tapping task. Participants are expected to use direct pointing as well as indirect cursor techniques to select a stereoscopic spherical target. The results show that, in the sense of a direct interaction technique, user recognition of an object appears to converge in the center of a simulated area. Unfortunately, this convergence is not demonstrated in the indirect cursor situation. The pointing estimation from the users is more accurate when using the indirect interaction approach. The findings provide an understanding of the interaction characteristics done by the users in the stereoscopic environment. Importantly, developers of a virtual environment may use the result when developing effective user interface perception in specific interaction techniques.